(untitled) (Comparatismi, 2025)
This essay aims to critically and theoretically examine literary genres within contemporary contexts, assessing whether and to what extent these genres remain applicable to works that are expansive, collaborative, and transmedia in nature, emerging from convergent culture. Over time, literary genres have assumed various functions, ranging from merely classificatory to normative, depending on the context and historical period. Genres have increasingly become tools for comparing works, evaluating them, and situating them within a specific literary landscape. In many cases, they have served both as a means of organizing the cultural system and as a mode for experimentation and artistic transformation. With the advent of convergent media, genres have undoubtedly undergone further changes, both theoretically and in practical application, as narrative techniques have increasingly focused on expanding storytelling across different media, each contributing to the extension of the product in its own specific ways. This study aims to explore both the theoretical and practical dimensions of genres within new forms of cultural production, particularly through the analysis of transmedia works, literary production platforms and fanfiction.